(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Banking sector is picked as it is very managed part in India. HDFC bank has biggest market capitalization among the managing account players which is quickly trailed by State bank of India (SBI) and ICICI bank. Since SBI is biggest PSU bank in India, ICICI bank and HDFC banks are considered for relative investigation so as to make a dimension playing field.